Molecular imaging: spawning a new melting-pot for biomedical imaging - Abdullah, Basri Johan Jeet (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, 2006)
Predicting the future is a dangerous undertaking at best, and not meant for the faint-hearted. However, viewing the advances in molecular medicine, genomics and proteomics, it is easy to comprehend those who believe that molecular imaging methods will open up new vistas for medical imaging. The knock on effect will impact our capacity to diagnose and treat diseases. Anatomically detectable abnormalities, which have historically been the basis of the practice of radiology, will soon be replaced by molecular imaging methods that will reflect the under expression or over expression of certain genes which occur in almost every disease. Molecular imaging can then be resorted to so that early diagnosis and characterisation of disease can offer improved specificity. Given the growing importance of molecular medicine, imagers will find it profitable to educate themselves on molecular targeting, molecular therapeutics and the role of imaging in both areas. © 2006 Biomedical Imaging and Intervention Journal. All rights reserved.